The design coordination role at the pre-construction stage of construction projects. Issue 4 (19th May 2022) - Ndekugri, Issaka; Ankrah, Nii A.; Adaku, Ebenezer
ABSTRACT: The importance of the concept of prevention through design (PtD) to the alleviation of the problem of poor health and safety (H&S) management in the construction industry is widely acknowledged. It has been adopted in the regulatory framework for H&S in the UK construction industry through the Construction Design and Management Regulations 2015 (CDM 2015) which place on the project client obligations with emphasis on coordination of H&S at the pre-construction stage of the project by a client-appointed 'Principal Designer' (PD). Unfortunately, research into the implementation of CDM 2015 into actual practice at the pre-construction stage has been patchy. The paper reports, with respect to the PD role, on part of research undertaken to respond to this gap. It involved surveys of clients and practitioners via fourteen focus group discussion sessions with over eighty participants to develop knowledge and understanding of the PD role. The research issues included: appointments to the role; structures for discharge of the role; day-to-day functions of the PD; remuneration arrangements; and common challenges regarding the PD.